A simple coloured indicator for monitoring ultra high pressure processing conditions - Fernández, Avelina; Butz, Peter; Corrales Moreno, Margarita; Lindauer, Ralf; Picouet, P.; Rodrigo, G.; Tauscher, Bernhard (Journal of food engineering, 2009)
Diels-Alder reactions between coenzyme Q(0) as dienophile and sorbic acid as diene compounds have been investigated under high pressure and temperature combinations. The reaction leads to a colour degradation of coenzyme Q(0), due to the formation of Diels-Alder adducts. The fact that this is a coloured reaction makes it suitable to be applied as indicator in high pressure treatments. The response to pressure and temperature was satisfactorily adjusted to a first order kinetic model in the pressure/temperature range where food safety and quality are crucial, as well as under conditions necessary to achieve ultra high pressure assisted thermal sterilization of foods. Furthermore, concentrations of both components could be systematically chosen to reveal the pressure and temperature achieved during the pressure assisted thermal sterilization processes. The proposed system is simple, coloured and based on non-toxic chemicals, and could thus become a useful tool for monitoring high pressure thermal processing conditions.